ALLELOPATHIC EFFECT OF DIGERA MURICATA (L.) MART. ON SEEDS OF MAIZE (International Journal of Food and Nutritional Sciences, 2022)
In nature, no plant is unproductive; in reality weeds are essential from the perspective of medicinal, allelopathic and food values. Weed infestation in crop fields cause loss to agriculture production. Thus, we were concentrated on allelopathic effect of a dominant weed in various crop fields i.e Digera muricata(L.) Mart. of Amaranthaceae family on “Kaveri” variety of Maize crop which is cultivating in several fields. To determine allelopathic effect on germination of selected crop aqueous leaf, stem and root extracts (0.0, 0.5, 1.0 and 5.0%) of the selected dominant weed Digera muricata was used. The present study revealed an inhibitory effect in seed germination at all concentrations of leaf, stem and root extracts. There was no effect on root growth at lower concentrations, but higher concentration (5%) was shown an inhibitory effect. Inhibitory effect on stem length was shown at all concentrations. But it was suggested to allow the growth of useful weeds for sustainable development of the country under Performance payments for environmental services (PES) schemes.